Enhancing effects of 60Co irradiation on the extraction and activities of phenolic components in edible Citri Sarcodactylis Fructus. (15th August 2023) - Wang, Siwei; Li, Yuxin; Qu, Ying; Guo, Ding; Luo, Shuai; Wang, Jingxia; Peng, Chaorong; Zhang, Xiaobin; Jiang, Hezhong
Graphical abstract: Highlights: 60 Co-γ ray irradiation is effective for extracting active chemicals in Citri Sarcodactylis Fructus (CSF), a functional food. Content of 7-hydroxycoumarin, hesperidin, 5, 7-dimethoxycoumarin, 5-methoxypsoralen was enhanced by 60 Co-γ ray irradiation. 60 Co-γ ray irradiation enhanced the antibacterial, anti-inflammatory, antioxidant, and anticancer properties of CSF. Abstract: In this study, the impact of 60 Co-γ ray irradiation treatment on the content of active chemicals and their functions in Citri Sarcodactylis Fructus (CSF) was assessed. Scanning electron microscopy, Fourier transform infrared spectroscopy, and γ-ray diffraction revealed physical structure changes in CSF powder. According to the findings, the content of total flavonoids in the ethanol extract of CSF increased by 9.5%–21.62%, 7-hydroxycoumarin, hesperidin, 5, 7-dimethoxycoumarin, and 5-methoxypsoralen increased by 5.31%–51.8%, 10.07%–99.81%, 6.6%–62.29%, and 3.03%–300%, respectively, when the irradiation dosage was raised, and the antibacterial, anti-inflammatory, antioxidant, and anticancer properties were all raised considerably. These results imply that the principal components and activity changes are proportional to the irradiation dosage. At present, the findings of this study serve as a reference for the use of irradiation technology in assisting extraction and enhancing the effects of functional foods.